The Effectiveness of Mobile Applications in Developing Students’ English Grammar Skills - Murtiningsih Sri Rejeki; Wati Nabila Putri Tosi Anggoro; Haryadi Didit (E3S Web of Conferences)
While grammar remains an important component of English language learning, many English as a Foreign Language (EFL) learners continue to struggle with mastering grammatical structures. Despite advancements in educational technology, traditional grammar instruction methods persist in many classrooms, potentially limiting students’ engagement and progress. This study investigates the effectiveness of mobile applications as a tool to enhance English grammar mastery among EFL learners. Using a quantitative experimental design, this investigation involved 45 junior high school students at a private school in Yogyakarta, divided into experimental (N=26) and control groups (N=19). The experimental group was exposed to grammar instruction through mobile applications, while the control group received other media-based instruction. Preand post-test assessments were administered to measure the impact on grammar proficiency. Contrary to expectations, the findings revealed no statistically significant improvement in the experimental group’s grammar performance compared to the control group, leading to the rejection of the initial hypothesis. This study underscores the complexity of integrating mobile technology in language education and suggests further research with extended exposure and varied application features to better understand the potential of mobile-assisted grammar learning.